Factors determining cognitive, motor and language scores in low birth weight infants from North India. - Ravi Prakash Upadhyay; Sunita Taneja; Suman Ranjitkar; Sarmila Mazumder; Nita Bhandari; Tarun Dua; Laxman Shrestha; Tor A Strand (PLoS ONE)
Background Children born with low birth weight (LBW) tend to have lower neurodevelopmental scores compared to term normal birth weight children. It is important to determine factors that influence neurodevelopment in these low birth weight children especially in the first 2-3 years of life that represents a period of substantial brain development. Methods This secondary data analysis was conducted using data from LBW infants enrolled soon after birth in an individually randomized controlled trial (RCT) and followed up till end of 1st year. Neurodevelopmental assessment was done at 12 months of corrected age by trained psychologists using Bayley Scales of Infant and Toddler Development 3rd edition (Bayley-III). Factors influencing cognitive, motor and language scores were determined using multivariable linear regression model. Results Linear growth (i.e., length for age z score, LAZ) [cognitive: Standardized ẞ-coefficient = 2.19, 95% CI; 1.29, 3.10; motor: 2.41, 95% CI; 1.59, 3.23; language: 1.37, 95% CI; 0.70, 2.04], stimulation at home [cognitive: 0.21, 95% CI; 0.15, 0.27; motor: 0.12, 95% CI; 0.07, 0.17; language: 0.21, 95% CI; 0.16, 0.25] and number of diarrhoeal episodes [cognitive: -2.87, 95% CI; -4.34, -1.39; motor: -2.62, 95% CI; -3.93, -1.29; language: -2.25, 95% CI; -3.32, -1.17] influenced the composite scores in all three domains i.e., cognitive, language and motor. While increase in LAZ score and stimulation led to increase in composite scores; an increase in number of diarrhoeal episodes was associated with decrease in scores. Weight for height z scores (WHZ) were associated with motor and language but not with cognitive scores. Additionally, a negative association of birth order with cognitive and language scores was noted. Conclusions The findings indicate the possible importance of promoting nutrition and preventing diarrhoea as well as ensuring optimal stimulation and nurturance at home for enhancing child development in LBW infants.